2019
DOI: 10.1111/soin.12276
|View full text |Cite
|
Sign up to set email alerts
|

When the Name Matters: An Experimental Investigation of Ethnic Discrimination in the Finnish Labor Market

Abstract: This article considers the possibilities and limits of human‐capital credentials in entering the labor market for immigrants in Finland. It reports findings of a correspondence study on how employers respond to job applicants of five different backgrounds who were otherwise equivalently matched on various demographic and human‐capital characteristics. The findings strongly indicate the continuing salience of ethnicity in securing employment opportunities in the Finnish labor market. Employers significantly pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 22 publications
0
32
0
1
Order By: Relevance
“…417). Moreover, another study found that individuals with a foreign surname are significantly less often selected for job interviews compared to individuals with a Finnish surname (Ahmad 2019). According to results from the Eurobarometer 2015, 67% of respondents in Finland estimated that discrimination based on ethnic background is common and 66% estimated that skin-color and ethnic background may affect employment decisions.…”
Section: Regulations Regarding Working In Finlandmentioning
confidence: 99%
“…417). Moreover, another study found that individuals with a foreign surname are significantly less often selected for job interviews compared to individuals with a Finnish surname (Ahmad 2019). According to results from the Eurobarometer 2015, 67% of respondents in Finland estimated that discrimination based on ethnic background is common and 66% estimated that skin-color and ethnic background may affect employment decisions.…”
Section: Regulations Regarding Working In Finlandmentioning
confidence: 99%
“…The literature shows that immigrant and minority job applicants are often overlooked in favor of native-born applicants [ 35 , 36 ]. Researchers from one study cited insufficient information during the hiring phase as a possible reason [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the municipality of Helsinki announced the use of English in public services, this is yet to be fully implemented meaningfully and on a wider scale. The Finnish language is an impediment in so many fronts as highlighted by the immigrants through a number of studies including in entrepreneurship (Yeasmin & Koivurova, 2019), discrimination (Ahmad, 2019). Channeling official communication using the Finnish and Swedish languages during the pandemic is a subtle prejudice practice and a subtle way of discrimination of disadvantaged minorities that are locked out in the information distribution through the official communication channels.…”
Section: Data Analysis Methodsologymentioning
confidence: 99%